Pentingnya Komunikasi Informasi Dan Edukasi Tentnag Gizi Seimbang Pada Ibu Hamil Trimester Pertama Kehamilan - Hamidah, Siti; Rizal, Muhammad Saiful (IJMT : Indonesian Journal of Midwifery Today, 2023)
3 months before marriage, a woman and a man must have an examination of their reproductive health. Likewise, when it is known that there is a delay in menstruation, you must immediately go for a check-up, to prevent problems in your pregnancy. However, this is not yet widely understood. The need for pregnant women regarding balanced nutrition is very important for the health of the mother and her fetus. The research design uses a pre-experimental research type, with a one group pretest - posttest design approach with proof of the implementation of activities. The population was all first trimester pregnant women who checked at PMB Siti Hamidah (80 pregnant women). Sampling technique with purposive sampling (60 pregnant women). The independent variable is the mother's knowledge of balanced nutrition using the IEC approach, while the dependent variable is the increase in the weight of the first trimester pregnant women. The measuring instrument used is the weight scale, analyzed by the Wilcoxon hypothesis test with α = 0.05. The statistical test results obtained a p value of 0.000 α = (0.05), so it was decided that H0 was rejected or H1 was accepted. The conclusion is that there is an influence of Information Communication and Education on the consumption of balanced nutrition in the first trimester of pregnant women which results in weight gain in the first trimester of pregnant women. 3 bulan sebelum pernikahan seorang wanita dan pria harus melakukan pemeriksaan tentang kesehatan reproduksinya. Demikian juga ketika diketahui adanya keterlambatan haid, harus segera memeriksakan diri, untuk mencegah terjadinya masalah dalam kehamilannya. Namun hal tersebut, belum banyak difahami. Kebutuhan ibu hamil tentang gizi seimbang sangat penting untuk kesehatan ibu dan janinnya. Desain penelitian menggunakan jenis penelitian pre eksperimen, dengan pendekatan one group pretest - posttest design dengan pembuktian pelaksanaan kegiatan. Populasi adalah semua ibu hamil trimester I yang periksa di PMB Siti Hamidah (80 ibu hamil). Tehnik sampling dengan Purposive Sampling (60 ibu hamul). Variabel Independen adalah pengetahuan ibu tentang gizi seimbang dengan pendekatan KIE, sedangkan variable dependennya adalah kenaikan BB ibu hamil trimester I. Alat ukur yang digunakan adalah timbangan BB, dianalisa dengan uji hipotesis Wilcoxon dengan α = 0,05. Hasil uji statistik di dapatkan p value 0,000 α = (0,05), maka diputuskan bahwa H0 ditolak atau H1 diterima. Kesimpulannya adalah ada pengaruh Komunikasi Informasi dan Edukasi terhadap konsumsi gizi seimbang ibu hamil trimester I yang berakibat pada kenaikan berat badan ibu hamil trimester I.